Profesjolekty jako źródło translacyjnych i kulturowych problemów tłumacza (na materiale Kolacji z zabójcą Aleksandry Marininy w tłumaczeniu Margarity Bartosik) - Letka-Spychała, Olga (Acta Polono-Ruthenica, 2018)
Professional dialect as a source of lexical and cultural problems of the interpreter is considered in the article. The author of the article analyses two groups of professional dialects: vocabulary connected with the militsiya rank structure and militsiya procedures in the best-selling Russian writer of criminal novels – Alexandra Marinina. Her first novel Confluence of Circumstances published in 1996 was material of the present analysis.